Nuwairi, Ibrahim. “The Historic Nature of the Movement of the Spread of Islam in the view of Shaykh Muhammad Al-Ghazali,” Year 4, Issue 14 (Fall 1419 AH/ 1998 CE), Pp. 113-137. - نويري, إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Ibrahim Nuwairi’s article explores the elements that make up Shaykh Muhammad al-Ghazali’s perspective on the historical spread of Islam through his many written contributions. It discusses the historical foundations for al-Ghazali’s interest in daʿwah (outreach or inviting to Islam), his discussions with certain Muslims and their beliefs on the concepts of jihad and war, and his assertion that peace is the basis of daʿwah in Islam and that freedom is the basis of Islam in action. It also discusses al-Ghazali’s refutation of the claims of Orientalists that Islam was spread by the sword and through military conquest, providing al-Ghazali’s understanding of Qur’anic verses related to daʿwah, wisdom, and fair preaching, while presenting certain concepts and views in al-Ghazali’s thought.